A new species of freshwater crab from the East Usambara Mountains of Tanzania, East Africa, with a redescription of Telphusa infravallata Hilgendorf, 1898 (Brachyura: Potamoidea: Potamonautidae) - Cumberlidge, Neil; Conners, Paige M. (Zootaxa, 2024)
This work describes a new species of freshwater crab from the East Usambara Mountains of Tanzania from previously unidentified museum material. A second species from these mountains, T. infravallata Hilgendorf, 1898, is redescribed based on reexamination of the type material, and its gonopods and mandible are illustrated for the first time. Diagnoses, illustrations, and a distribution map are provided for these species.